Q: If 3 plus y equals a 3-y equals a then a equals y equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

y = -1

x = 3 and y = 0

Y = 1 3(1) = 3 26 + 3 = 29

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

x=1y=2x+3y=2*1 + 3y=5

Related questions

2y + 3 = 3y + 9 2y - 3y = 9 - 3 or -y = 6 so y = -6

4x+3/3=y

3y - 3 = 2y + 5 3y - 2y = 5 + 3 y = 8

2x+3y=13 3x-y=3 x=2

y = -1

x = 3 and y = 0

Y = 1 3(1) = 3 26 + 3 = 29

3y + 8 = 3 -8 -8 3y=-5 (3y)/3=-5/3 y=(-5/3)

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

4x + 3y=9 x=0 y=3

x=1y=2x+3y=2*1 + 3y=5

2x + 3y = 1 y = 1/3 - 2x/3